The “sweet” side of a long pentraxin: how glycosylation affects PTX3 functions in innate immunity and inflammation - Inforzato, Antonio; Reading, Patrick C.; Barbati, Elisa; Bottazzi, Barbara; Garlanda, Cecilia; Mantovani, Alberto (Frontiers in Immunology, 2013)
Innate immunity represents the first line of defence against pathogens and plays key roles in activation and orientation of the adaptive immune response. The innate immune system comprises both a cellular and a humoral arm. Components of the humoral arm include soluble pattern recognition molecules (PRMs) that recognise pathogen associated molecular patterns (PAMPs) and initiate the immune response in coordination with the cellular arm, therefore acting as functional ancestors of antibodies. The long pentraxin PTX3 is a prototypic soluble PRM that is produced at sites of infection and inflammation by both somatic and immune cells. Gene targeting of this evolutionarily conserved protein has revealed a non-redundant role in resistance to selected pathogens. Moreover, PTX3 exerts important functions at the crossroad between innate immunity, inflammation and female fertility. The human PTX3 protein contains a single N-glycosylation site that is fully occupied by complex type oligosaccharides, mainly fucosylated and sialylated biantennary glycans. Glycosylation has been implicated in a number of PTX3 activities, including neutralization of influenza viruses, modulation of the complement system, and attenuation of leukocyte recruitment. Therefore, this post translational modification might act as a fine tuner of PTX3 functions in native immunity and inflammation. Here we review the studies on PTX3, with emphasis on the glycan-dependent mechanisms underlying pathogen recognition and crosstalk with other components of the innate immune system.